Paracanthonchus multisupplementatus sp. n. and Cyatholaimus minor sp. n. (Nematoda) from the coast of Vietnam - Gagarin, Vladimir G. (Zootaxa, 2012)
Two nematode species found on the coast of Vietnam are described and illustrated. Paracanthonchus multisupplementatussp. n. is morphologically close to P. multitubifer Timm, 1961, but differs from it the longer and slender tail (c = 9.1–11.0,c’ = 3.0•–3.4 in males, c = 8.1–8.7, c’ = 3.6–4.1 in females versus c = 11.4–14.0, c’ = 2.3–2.8 in males, c = 10.2–10.4, c’= 2.1–2.8 in females), bigger dorsal tooth in stoma, larger diameter of amphidial fovea (40–55% of corresponding bodywidth versus 15% of corresponding body width), longer spicules and gubernaculum (spicules 56–61 µm long, gubernac-ulum 36–43 µm long versus spicules 36 µm long, gubernaculum 28 µm long) and more number of supplement organs(57–62 in number versus 21–22 in number). Cyatholaimus minor sp. n. is close related to C. ocellatus Bastian, 1865, butis clearly distinct in the shorter body (L = 532–710 µm versus L = 1100–1790 µm), slenderer tail (c’ = 3.5–4.3 versus c’= 2.5–2.8), bigger dorsal tooth in stoma and shorter spicules and gubernaculum (spicules 21–22 µm long, gubernaculum 19–20 µm long versus spicules 60 µm long, gubernaculum 52 µm long).